Assessment on Cases Operated Due to Postmenopausal Adnexal Masses - İriş, Aslı and Aydoğan Kırmızı, Demet and Taner, Cüneyt Eftal and Üstünay, Elif (Gynecology Obstetrics & Reproductive Medicine, 2012)
OBJECTIVE: The objective was to evaluate the clinical traits, as well as preoperative and postoperative histopathologic findings of patients who are operated due to adnexal mass during postmenopausal period. STUDY DESIGN: Our study incorporates 204 patients who were operated at our hospital due to adnexal masses during postmenopausal period. Clinical details (age, parity, personal and family history, oral contraceptive and smoking status) of all patients are recorded. Measurement of serum ca 125 values and trans-vaginal or trans-abdominal ultrasonography findings are recorded, as well as morphological features of each adnexal mass. The tissue material removed in operation was analyzed in histopathologic terms. Preoperative findings are compared with histopathologic diagnosis. RESULTS: According to pathologic examinations, the results for 76.5% of 204 patients (n=156) operated due to postmenopausal adnexal mass were benign, whereas the remaining 48 patients (23.5%) had malign results. The most common pathological examination result in the patients was serous cystadenoma (n=62; %30.4) (p<0.05). In malign cases, serous adenocarcinoma was encountered the most (n=24; %50.1) (p<0.05). The analyses on adnexal masses which are evaluated via preoperative ultrasonography showed that cyst diameter, its capsule thickness and - if any - septa thickness was more common in malign cases. In addition, multilobulation, the septa formation, papillary formation, semisolid formation, the presence of bilaterality and ascites were more common in masses in malign group (p<0.05). Average ca 125 level was 27.9 IU/ml and 699.6 IU/ml (p<0.05) in benign and malign groups, respectively. CONCLUSION: Serum ca 125 levels and TVUSG are useful diagnostic procedures in evaluating especially postmenopausal adnexal masses, however, the definitive diagnosis regarding adnexal masses should be made via histopathologic analysis.